2003
DOI: 10.11606/issn.2316-9079.v2i1p35-41
|View full text |Cite
|
Sign up to set email alerts
|

Uso do hábitat e alimentação em juvenis de Bothrops jararaca (Serpentes, Viperidae) na Mata Atlântica do sudeste do Brasil

Abstract: Introdução A dieta é uma das principais dimensões do nicho de uma serpente e pode influenciar o uso de hábitat, seu comportamento alimentar e seu período de atividade (Toft 1985

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
30
3
18

Year Published

2009
2009
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 32 publications
(56 citation statements)
references
References 11 publications
3
30
3
18
Order By: Relevance
“…Thus, comparing the data obtained by this experiment with the available literature, it is possible to conclude that the findings described here confirm that the predominant esophagus-lining epithelium of the studied samples was prismatic simple epithelium, which is compatible with previous works (FRYE, 1991;ABDEEN et al, 2013), although no pseudo-stratified epithelium has been found, as described by Khamas and Reeves (2011). The morphology of the esophageal epithelial cells seemed to undergo changes: while the cells were oval and round in the cranial portions, they were longer in the caudal esophagus portion.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Thus, comparing the data obtained by this experiment with the available literature, it is possible to conclude that the findings described here confirm that the predominant esophagus-lining epithelium of the studied samples was prismatic simple epithelium, which is compatible with previous works (FRYE, 1991;ABDEEN et al, 2013), although no pseudo-stratified epithelium has been found, as described by Khamas and Reeves (2011). The morphology of the esophageal epithelial cells seemed to undergo changes: while the cells were oval and round in the cranial portions, they were longer in the caudal esophagus portion.…”
Section: Discussionsupporting
confidence: 92%
“…Bothrops jararaca has a broad distribution in southeastern South America (ALMEIDA-SANTOS, 2005); In Brazil it is usually associated with the Atlantic Forest and anthropogenic areas (HARTMANN et al, 2003). The jararaca is a viviparous, semi-arboreal, and nocturnal snake that is most active during the rainy season.…”
Section: Introductionmentioning
confidence: 99%
“…Indivíduos repousando foram encontrados sob monte de lenha (N = 1), dentro de buraco em barranco na borda da mata (N = 1), em galpão (N = 1) e sobre a vegetação (N = 1). A dieta é composta principalmente de anuros nos filhotes e pequenos mamíferos nos adultos (Sazima 1992, Hartmann et al 2003. Encontramos roedores (N = 4) e vestígios de mamíferos (pêlos; N = 6).…”
Section: Bothrops Jararacaunclassified
“…Sua dieta apresenta variação ontogenética, já que indivíduos jovens alimentam-se de quilópodes, lagartixas, filhotes de roedores e principalmente anuros, enquanto os adultos geralmente predam roedores. Bothropoides jararaca é vivípara e gera de 5 a 16 filhotes (Sazima, 1992;hartmann et al, 2003). Segundo Lema (1994), no Rio Grande do Sul, é muito frequente nas poucas regiões florestadas do norte, atingindo a Encosta Inferior do Nordeste até Porto Alegre.…”
unclassified